The California Border Health Collaborative: A Strategy for Leading the Border to Better Health - Charles Edwards Matthews III; Charles Edwards Matthews III; Wilma eWooten; María Gudelia Rangel Gomez; Justine eKozo; April eFernandez; Victoria eOjeda (Frontiers Media S.A., 2015)
There are hundreds of departments and organizations working on border health issues in the California/Baja California border region trying to protect and improve health without a collaborative structure that integrates jurisdictions and organizations. As a result, there is a need to effectively improve the health in the border region by coordinating these organizations to work together and benefit from each other's best practices. The newly developed California Border Health Collaborative (CBHC) can provide the leadership and collaborative culture to positively improve the health of the border region. This article aims to describe the development process of this collaborative to include key ingredients to success, the roles of mulit-level jurisdictions, and policy implications.This article describes the methods used to develop key aspects of collaborative leadership, strategic alignment and a common vision toward the building of this collective impact approach to border health. In addition, we describe the role of key local County (County of San Diego Live Well San Diego initiative), State, (California Department of Public Health- Office of Binational Border Health), Federal (US-Mexico Border Health Commission's Leaders across Borders), Academia (e.g., University of California San Diego and San Diego State University) and non-profit entities (e.g., Project Concern International, San Ysidro Health Center) in forming the BHCC. Evaluating the consortium development process included a literature review of similar processes, a review of internal documents and an analysis of developmental events. To this point the CBHC has built a strong, cohesive collaborative on the U.S. side of the border. It is sharing and leveraging local expertise to address many border health issues. Even more importantly, the BHCC has reached a key stage in which it can effectively engage its Baja California, Mexico counterparts in a manner that will prove extremely powerful